Pengaruh Good Governance, Gaya Kepemimpinan, Komitmen Organisasi dan Budaya Organisasi Terhadap Kinerja Pemerintah Daerah (Studi Pada Pemerintah Daerah Kabupaten Kampar) - Siti Aisyah; Kirmizi '; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the effect of good governance, leadership style, organizational commitment and organizational culture on the performance of local government in District Government of Kampar. The research samples are selected by using questionnaire survey method were 18 manager in the special district of Kampar. The analytical tool used is multiple regression. The result showed show that: (1) good governance has positive influence on the performance of local government, (2) leadership style has positive influence on the performance of local government (3) organizational commitment has positive influence on the performance of local government (4) organizational culture does not affect the performance of local government.Keywords: Good governance, leadership style, organizational commitment and Organizational culture, performance of local government